Relief of Shoulder, Arm, Forearm and Hand Pain Due to Left Subclavicular Cardiac Pacemaker Placement by Chiropractic Adjustments–A Safe and Rapidly Effective Strategy: Case Report - DC, DACNB, William Rogers; Peppard DC, Dean; MD, PhD, David Morrison (Clinical Medicine And Health Research Journal, 2024)
Unintended but common consequences of pace maker placement or insertion include shoulder dysfunction and pain. This is not something that cardiologist or electrophysiology specialist will be familiar with terms of treatment once these problems become manifest. Cross discipline collaboration as reported in this case resulted in the relief of discomfort caused by pace maker insertion induced shoulder dysfunction. This procedure was safe and rapidly affective.